DESIGN OF 8-STORY REINFORCED CONCRETE STRUCTURE OF WANGGUH APARTMENT PONTIANAK BUILDING WITH COMPARISON OF BEAM REVIEW - Lunardi, Felix; Aryanto, Aryanto; Yusuf, Muhammad (Jurnal Teknik Sipil, 2024)
The article highlights the pivotal role of housing in Pontianak's economic growth, driven by its status as a regional hub attracting residents for employment, education, and services, leading to a significant demand for housing, including apartments. The study specifically focuses on the detailed design of the Wangguh Apartment Building, emphasizing safety and efficiency in response to urban development needs. The project exemplifies modern urban development efforts by aiming to create sustainable living environments.Additionally, the research compares beam designs in multi-story buildings to optimize structural integrity, stability, and load-bearing capacity while adhering to Indonesian National Standards (SNI). The study emphasizes the importance of seismic considerations given Pontianak's classification as a new earthquake zone, with detailed planning ensuring durability and safety against seismic forces. The process involves site classification, seismic design category determination, and structural system selection, with thorough structural modeling and analysis to meet stringent standards and ensure resilience. The study contributes valuable insights into reinforced concrete design and construction through meticulous calculations and adherence to standards, aiming to enhance future residential projects' effectiveness and sustainability in Pontianak City.